PENGENDALIAN SOSIAL PELANGGARAN TATA TERTIB SANTRIWATI DI PONDOK PESANTREN DARUL KHAIRAT PONTIANAK - Destriani, Susi; Rustiyarso, Rustiyarso; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe objective of this research was to know the effect of social control on violations of rules for santriwati In Darul Khairat Islamic Boarding School Pontianak through preventive, repressive, curative action, and the most effective social control. This research used qualitative approach with descriptive method. The data collection techniques were observation, interview and documentation study using data collection tools such as observation guide, interview guide and documentation. Research results proved that (1) social control through preventive action by administrators on santriwati was not well responded by santriwati. (2) social control through repressive action by administrators for santriwati could give a deterrent effect and the emergence of shyness for santriwati to repeat the violation. (3) social control through curative action by administrators for santriwati which was given after the violation could give a deterrent effect after the punishment. (4) The most effective social control was to provide punishment in the forms of reciting the Qur?an 1 juz, memorizing juz amma, cleaning the boarding yard, cleaning the WC, and went around the boarding yard with sholawat reading which resuscitated santriwati not to repeat the violation in the islamic boarding school. Keywords: social control, violations of rules, santriwati of islamic boarding school